Modelling a Christian Academy: Christ, Disciples, and Biblical Scholarship in Origen’s Commentary on Matthew - Solheid, John ca. 20./21. Jh. (Vigiliae Christianae, 2022)
This paper addresses evidence in Origen’s Commentary on the Gospel of Matthew of the Alexandrian’s self-understanding of his scholastic practices. Drawing on Origen’s interpretation of the parables in the Gospel, I argue that Origen exploits the motif of Jesus explaining the parables to his disciples as a model for his own school enterprise in Caesarea. In light of this observation, I will begin by examining the echoes of the classroom environment found in Origen’s Matthew Commentary building on the work of Guido Bendinelli and Lorenzo Perrone. Paying particular attention to stylistic features, such as the use of the first-person plural, I will map the classroom dynamic in the making of the commentary. Then, I will focus on Origen’s hermeneutical approach to Jesus’ parables, especially the distinction he draws between Jesus engagement with the “crowds” and his private teaching to the disciples. Underpinning the Matthew Commentary was Origen’s attempt to model his school against the conceptual backdrop of the Jesus-disciple dynamic and the Greco-Roman philosophical school tradition.